Efektywność współczesnych koncepcji i metod zarządzania - Haus, Ber (Effectiveness of Modern Conceptions and Methods of Management, 2006)
The author underlined that sole concepts and methods of management are not effective. But effective are projects introduced within companies. Following publications, the author described some effects which are typical for methods of management and their bases. It was underlined that the lean management method embraces other methods of management. It was explained where are the sources of such effects. Almost every company tends to the effectiveness with the use of different methods of management, not knowing that the method used by it is well known method of management
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 47-56